PROSPEK DAN POTENSI PEMANFAATAN KAYU KARET SEBAGAI SUBSTITUSI KAYU ALAM - Boerhendhy, Island; Nancy, Cicilia; Gunawan, Anang (Jurnal Ilmu dan Teknologi Kayu Tropis, 2003)
Wood from natural forest for processing industry is decreasing in term of quality and volume. Due to technology development on processing and preservation for rubber wood, the range of rubber wood utilization is widen, so the demand of its increases. The potency of rubber wood as raw material for wood industry is high. In 1997, the area of rubber plantation was about 3.4 million hectares. If 3 percent of big estate and 2 percent of smallholder areas would be replanted every year, it could provide 2.7 million m3 of rubber wood per year. Rubber wood management in the field faced constraints, such as road access for smallholder field, low rendement, supply of rubber wood is only available at certain season, and a distance between processing location and rubber areas is far, and therefore the economic value of rubber wood becomes lower. Availability of good road access, utilization of clonal planting material, proper tapping practice, replanted area is located in one large area, and positive support by government are the steps to be taken by various agencies in order to optimize the utilization and economic value of rubber wood.